Current higher agricultural education in Poland – threats and challenges (Case studies: Europe 2) - Stypinski P. (Agricultural higher education in the 21st century : a global challenge in knowledge transfer to meet world demands for food security and sustainability, 2015)
The future role of agriculture in Europe will be not less important than it is at present and additionally we should be ready for uncertainty and threats (droughts, floods, social or political conflicts, crop failure but also crop surplus) regarding agro-food systems. Therefore farmers and advisers must be very well educated and prepared to the act in modern agricultural and food processing systems. The number of agriculture students and graduates has decreased recently, one of the reasons being the problem with jobs in agriculture sector and traditional programmes offered by Universities which do not fulfil the market demands and employers expectations. The modern agricultural universities and colleges should teach the biological bases of production and pay more attention to society needs and demands instead of typical technological knowledge which is very often offered by international firms and companies. Reform of higher agricultural education is absolutely necessary but it is clear that it will be successful only if it is supported by students and university staffs.
International Conference : Agricultural Higher Education in the 21st Century, 2015/06/15-17, Zaragoza (Spain)